Advancing Hydrovoltaic Energy Harvesting from Wood through Cell Wall Nanoengineering. (22nd November 2022) - Garemark, Jonas; Ram, Farsa; Liu, Lianlian; Sapouna, Ioanna; Cortes Ruiz, Maria F.; Larsson, Per Tomas; Li, Yuanyuan
Abstract: Converting omnipresent environmental energy through the assistance of spontaneous water evaporation is an emerging technology for sustainable energy systems. Developing bio‐based hydrovoltaic materials further pushes the sustainability, where wood is a prospect due to its native hydrophilic and anisotropic structure. However, current wood‐based water evaporation‐assisted power generators are facing the challenge of low power density. Here, an efficient hydrovoltaic wood power generator is reported based on wood cell wall nanoengineering. A highly porous wood with cellulosic network filling the lumen is fabricated through a green, one‐step treatment using sodium hydroxide to maximize the wood surface area, introduce chemical functionality, and enhance the cell wall permeability of water. An open‐circuit potential of ≈140 mV in deionized water is realized, over ten times higher than native wood. Further tuning the pH difference between wood and water, due to an ion concentration gradient, a potential up to 1 V and a remarkable power output of 1.35 µW cm −2 is achieved. The findings in this study provide a new strategy for efficient wood power generators. Abstract : Efficient hydrovoltaic wood power generators are fabricated based on highly porous wood with cellulosic nanofibril network filling the lumen through wood cell wall nanoengineering using a green, one‐step NaOH treatment. pH‐responsive device performance is observed with a potential up to 1 V and a remarkable power output of 1.35 µW cm −2 achieved under ambient conditions.